Effect of Work Experience and Motivation on Employee Performance at PT. Agro Sinergi Nusantara (ASN) Ujong Beurasok West Aceh - Maisuri, Novia Eka; Rusdi, Rusdi (Ridwan Institute, 2021)
This research is one of the human resources research that includes the application of scientific methods to find out the truth about human resource management. This study is one of the quantitative research taking the number of respondents, namely as many as 31 employees at the head office of PT. Agro Sinergi Nusantara Ujong Beurosok Aceh Barat, in the sampling process using the Saturated Sampling technique, where library research, interviews and questionnaires or questionnaires have been prepared in advance before conducting research. There are two independent variables in this research process, namely work experience and motivation and the dependent variable, namely employee performance, which is tested by multiple linear regression analysis. Based on the results of the hypothesis test, it is known that the work experience variable and the motivation variable have a positive and significant effect simultaneously on the employee performance variable at the head office of PT. Agro Sinergi Nusantara Ujong Beurosok Aceh Barat, but partially the work experience variable has a significant and positive effect on the employee performance variable at the head office of Pt. Agro Sinergi Nusantara Ujong Beurosok Aceh Barat, Work motivation has a significant and positive effect on employee performance at the head office of PT. Agro Sinergi Nusantara Ujong Beurosok Aceh Barat